2013
DOI: 10.1080/13632469.2013.781557
|View full text |Cite
|
Sign up to set email alerts
|

Displacement-Controlled Behavior of Asymmetrical Single-Story Building Models

Abstract: Displacement controlled behavior is a feature of low to moderate seismicity areas where the peak displacement demand on structures could be limited despite significant structural strength and stiffness degradation. In this article, the extension of the displacement controlled phenomenon to torsionally unbalanced framing systems is investigated. It is shown that the displacement demand of critical elements within a building can be insensitive to changes in eccentricity and torsional stiffness properties. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The PSHA acceleration design spectra was fi rst transformed into acceleration-displacement response spectra format using the approach in the commentary to AS1170.4-2007. A 1500-year maximum response spectrum displacement (RSD max ) of 95 mm was obtained which corresponded to a T 2 corner period of 1.5 s. Torsional amplifi cation was accounted for using procedures outlined by Lumantarna et al (2008;2013), incorporating a two-way asymmetric torsional amplifi cation factor  DD of 1.7 giving a conservative estimate of peak drift demand (PDD) =  DD RSD max = 160 mm. It was found that drift estimates determined using upper bound displacement methods were typically 10% lower than those obtained from the ETABS response spectrum analysis.…”
Section: Seismic Modelling and Analysismentioning
confidence: 99%
“…The PSHA acceleration design spectra was fi rst transformed into acceleration-displacement response spectra format using the approach in the commentary to AS1170.4-2007. A 1500-year maximum response spectrum displacement (RSD max ) of 95 mm was obtained which corresponded to a T 2 corner period of 1.5 s. Torsional amplifi cation was accounted for using procedures outlined by Lumantarna et al (2008;2013), incorporating a two-way asymmetric torsional amplifi cation factor  DD of 1.7 giving a conservative estimate of peak drift demand (PDD) =  DD RSD max = 160 mm. It was found that drift estimates determined using upper bound displacement methods were typically 10% lower than those obtained from the ETABS response spectrum analysis.…”
Section: Seismic Modelling and Analysismentioning
confidence: 99%
“…The issues with analysis of the torsional response of the dual system have been recognized as early as in the forties by Chitty [2]. Multiple attempts were made afterwards to generate simpler solutions mainly by considering numbers of simplified assumptions: the seismic load is taken by elements of the SW system and gravity load is taken by the MRF system [3,4], considering responses due to only fundamental mode [5], considering only two-dimensional motion [6], and idealizing multi-storey building into a single-storey model [7][8][9][10][11]. Because of these simplified assumptions, these studies have a very limited range of real application; for example: given that the stiffness parameters of the building can vary from floor to floor, using a single storey model resulted in an inaccurate estimation of these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Many earlier investigations based on linear elastic analyses were aimed to develop a quasi-static analysis approach to simulate dynamic torsional behaviour of asymmetrical buildings [8][9][10][11][12]. More recent studies based on non-linear analyses focussed on evaluating existing approaches recommended by design provisions and published literature in predicting the torsional behaviour of asymmetrical buildings [13][14][15][16][17][18]. The major shortcoming of analytical investigations reported in the literature was the idealisation of the building into a single-storey floor model.…”
Section: Introductionmentioning
confidence: 99%